Strategies for enhancing cancer chemodynamic therapy performance. Issue 2 (7th March 2022) - Jana, Deblin; Zhao, Yanli
Abstract: Chemodynamic therapy (CDT) has emerged to be a frontrunner amongst reactive oxygen species‐based cancer treatment modalities. CDT utilizes endogenous H2 O2 in tumor microenvironment (TME) to produce cytotoxic hydroxyl radicals (OH) via Fenton or Fenton‐like reactions. While possessing advantages such as tumor specificity, no need of external stimuli, and low side effects, practical applications of CDT are still impeded owing to the heterogeneity, complexity, and reductive environment of TME. Over the past couple of years, strategies to enhance CDT for efficient tumor regression are in rapid development in synergy with the growth of nanomedicine. In this review, we initially outline the fundamental understanding of Fenton and Fenton‐like reactions and their relationship with CDT. Subsequently, the development in the design of nanosystems for CDT is highlighted in a general manner. Furthermore, recent advancement of the strategies to augment Fenton reactions in TME for enhanced CDT is discussed in detail. Finally, perspectives toward the future development of CDT for better therapeutic outcome are presented. This review is expected to draw attention for collaborative research on CDT in the best interest of its future clinical applications. Abstract : Chemodynamic therapy (CDT) utilizes endogenous H2 O2 in tumor microenvironment to produce cytotoxic hydroxyl radicals through Fenton or Fenton‐like reactions. This review outlines the fundamental understanding of Fenton and Fenton‐like reactions and their relationship with CDT and highlights recent research advancements in the design of nanosystems to augment Fenton or Fenton‐like reactions for enhanced CDT. Perspectives toward the future development of CDT strategies for higher therapeutic outcome are also discussed.